2010
DOI: 10.1371/journal.pone.0013727
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium berghei Circumvents Immune Responses Induced by Merozoite Surface Protein 1- and Apical Membrane Antigen 1-Based Vaccines

Abstract: BackgroundTwo current leading malaria blood-stage vaccine candidate antigens for Plasmodium falciparum, the C-terminal region of merozoite surface protein 1 (MSP119) and apical membrane antigen 1 (AMA1), have been prioritized because of outstanding protective efficacies achieved in a rodent malaria Plasmodium yoelii model. However, P. falciparum vaccines based on these antigens have had disappointing outcomes in clinical trials. Discrepancies in the vaccine efficacies observed between the P. yoelii model and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 49 publications
4
30
0
Order By: Relevance
“…Although immunization with PfMSP-1 19 induced memory antibody responses that reacted strongly with the native PfMSP-1 19 on the blood-stage parasite, antibodies were not effective at protecting mice against P. berghei transgenic parasite challenge infection. PfMSP-1 19 -specific memory B cells failed to reduce the parasite load significantly and did not prolong the survival time of the infected mice, consistent with findings reported earlier (51). A previous study had shown that the significant reduction in numbers of Plasmodium yoelii MSP-1 19 -specific ASCs was because MBCs either underwent early apoptosis or were not activated after antigen reexposure, which subsequently resulted in death of the MBCs (49).…”
Section: Discussionsupporting
confidence: 89%
“…Although immunization with PfMSP-1 19 induced memory antibody responses that reacted strongly with the native PfMSP-1 19 on the blood-stage parasite, antibodies were not effective at protecting mice against P. berghei transgenic parasite challenge infection. PfMSP-1 19 -specific memory B cells failed to reduce the parasite load significantly and did not prolong the survival time of the infected mice, consistent with findings reported earlier (51). A previous study had shown that the significant reduction in numbers of Plasmodium yoelii MSP-1 19 -specific ASCs was because MBCs either underwent early apoptosis or were not activated after antigen reexposure, which subsequently resulted in death of the MBCs (49).…”
Section: Discussionsupporting
confidence: 89%
“…In all experiments, rPbSEA-1A generated significant protection. These results represent the first example of significantly reduced parasitemia and delayed mortality after vaccination with a blood-stage antigen in P. berghei ANKA (21). …”
Section: Vaccination With Pbsea-1 Protects Mice From P Berghei Anka mentioning
confidence: 68%
“…Our strategy for evaluation of the BDES multistage vaccine used appropriately designed and phenotyped transgenic rodent malaria parasites for assessing murine immune responses to individual antigenic targets from a human malaria parasite. We and other groups have developed several transgenic rodent malaria parasites expressing human malaria antigens (e.g., PfCSP, PfMSP-1 19 , Pfs25, and Pvs25) to evaluate the immunogenicity and/or protective efficacy of vaccines (13,(15)(16)(17)(27)(28)(29)(30). Here, we describe the successful development of PvCSP [PvCSP(Sal)/Pb] transgenic P. berghei parasite expressing the full-length PvCSP-(Sal) in place of the natural P. berghei counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Such transgenic parasites provide a safe, cheap, and more practical alternative to using nonhuman primate models for preclinical challenge studies of malaria vaccine efficacy. Our previous studies have shown that BDES was an effective malaria vaccine platform for all three stages of the parasites, including the pre-erythrocytic stage (12,13), asexual blood stage (14,15), and sexual stage (16,17), when transgenic P. berghei parasites expressing human Plasmodium antigens were used for their evaluation. If optimized, BDES vaccines could be adopted for developing potent multistage malaria vaccines.…”
mentioning
confidence: 99%